XXI CENTURY UZBEK THEATRE ART: PROBLEMS AND SOLUTIONS - Ochilova Kamola Ilhom kizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes the specific features of theatre art, its history and 21st century Uzbek theatre art information is provided. Theatre art life, dramatic behavior of events, various struggles and conflicts, inner experiences in actions, the actor reflects through his performance. It relies on the play or libretto written by the writer.